OF EQUAL DIGNITY: An Interpretation of Orientalium Ecclesiarum - Joseph, Jaisy (Asian Horizons, 2014)
Resisting a reduction of the conciliar event to an arbitrary power struggle between liberals and conservatives, Ormond Rush proposes a three-fold conciliar hermeneutic. First, a diachronic reading studies the development of ideas and documents before and during the council. Then, a synchronic reading analyzes a particular passage in relation to other conciliar texts. Finally, a hermeneutic of reception identifies the reception of the text into the life of the Church. This essay will apply only the first two readings to section 3 of Orientalium Ecclesiarum. The following will exegete this passage through a description of the relationship between Eastern and Western churches preceding the Council, an analysis of the development from the preparatory schema De Ecclesiis Orientalibus to the final draft of Orientalium Ecclesiarum, and the relationship of this passage to other conciliar texts related to the themes of local and universal Church, catholicity, and ecumenism.